Associations between attainment of incentivised primary care indicators and emergency hospital admissions among type 2 diabetes patients: a population-based historical cohort study. (June 2021) - Gunn, Laura H; McKay, Ailsa J; Molokhia, Mariam; Valabhji, Jonathan; Molina, German; Majeed, Azeem; Vamos, Eszter P
Objectives: England has invested considerably in diabetes care over recent years through programmes such as the Quality and Outcomes Framework and National Diabetes Audit. However, associations between specific programme indicators and key clinical endpoints, such as emergency hospital admissions, remain unclear. We aimed to examine whether attainment of Quality and Outcomes Framework and National Diabetes Audit primary care diabetes indicators is associated with diabetes-related, cardiovascular, and all-cause emergency hospital admissions. Design: Historical cohort study. Setting: A total of 330 English primary care practices, 2010–2017, using UK Clinical Practice Research Datalink. Participants: A total of 84, 441 adults with type 2 diabetes. Main Outcome Measures: The primary outcome was emergency hospital admission for any cause. Secondary outcomes were (1) diabetes-related and (2) cardiovascular-related emergency admission. Results: There were 130, 709 all-cause emergency admissions, 115, 425 diabetes-related admissions and 105, 191 cardiovascular admissions, corresponding to unplanned admission rates of 402, 355 and 323 per 1000 patient-years, respectively. All-cause hospital admission rates were lower among those who met HbA1c and cholesterol indicators (incidence rate ratio = 0.91; 95% CI 0.89–0.92; p  < 0.001 and 0.87; 95% CI 0.86–0.89; p  < 0.001), respectively), with similar findings for diabetes and cardiovascular admissions. Patients who achieved the Quality and Outcomes Framework blood pressure target had lower cardiovascular admission rates (incidence rate ratio = 0.98; 95% CI 0.96–0.99; p  = 0.001). Strong associations were found between completing 7–9 (vs. either 4–6 or 0–3) National Diabetes Audit processes and lower rates of all admission outcomes ( p -values < 0.001), and meeting all nine National Diabetes Audit processes had significant associations with reductions in all types of emergency admissions by 22% to 26%. Meeting the HbA1c or cholesterol Quality and Outcomes Framework indicators, or completing 7–9 National Diabetes Audit processes, was also associated with longer time-to-unplanned all-cause, diabetes and cardiovascular admissions. Conclusions: Attaining Quality and Outcomes Framework-defined diabetes intermediate outcome thresholds, and comprehensive completion of care processes, may translate into considerable reductions in emergency hospital admissions. Out-of-hospital diabetes care optimisation is needed to improve implementation of core interventions and reduce unplanned admissions.